National Culture, Creativity, and Productivity: What's the Relationship with Student Achievement?. Issue 4 (1st October 2016) - Fang, Zheng; Xu, Xianxuan; Grant, Leslie W.; Stronge, James H.; Ward, Thomas J.
Abstract : Using Hofstede's culture dimensions and World Values Survey (WVS) dimensions, the study uses a series of multiple regressions to explore the relationship among national culture, creativity as measured by patents, economic productivity as measured by gross domestic product per capita, and student achievement as measured by Trends in International Mathematics and Science Study. The findings of this exploratory study highlight long-term orientation value from Hofstede's national culture dimensions and tradition versus secular-rational values from the WVS as the most significant predictors of student academic achievement. A series of 12 regression analyses indicated significant relationships among student achievement, creativity, and economic productivity with models explaining between 19.9% and 76.0% of the variance among countries.